Neuropsychological and Emotional Deficits as Predictors of Correctional Treatment Response in Maryland, 2003-2005 ([Verlag nicht ermittelbar], 2008)
The study was designed to elucidate underlying neuropsychological and emotional regulatory mechanisms in variable responses to a cognitive-behavioral therapy (CBT) program among prison inmates. This study tested the hypotheses that performance deficits in executive cognitive function (ECF) tasks and emotional responses will characterize aggressive and disruptive inmates and predict treatment response. All subjects were examined using noninvasive behavioral, psychological, ECF, and hormone tests. The data contain a total of 232 cases. Inmates volunteering to participate in the cognitive-behavioral therapy (CBT) program offered by the Maryland correctional system were recruited from three facilities using a pseudo-random selection procedure during intake into the program. Consenting inmates received an extensive baseline testing battery of several complementary dimensions of higher order neuropsychological functions as well as conditions that influence them: (1) three ECF tasks and one emotional perception task, (2) collection of salivary cortisol during an acute stress task and the Symptom Checklist 90 (SCL-90) taken beforehand, (3) a short general neuropsychological test, (4) three psychological questionnaires, (5) an historical inventory to assess prior drug use and child and family background, and (6) a treatment readiness, responsivity, and gain scale. An events inventory and a success inventory were also administered. Several additional tests were administered repeatedly throughout treatment. A record review was conducted after program completion to ascertain incidents of institutional misconduct as well as treatment performance outcomes. Variables include IQ, demographics, background information, prior drug use, early trauma, psychopathy, aggression, stressful events, success, reactions to provocation, treatment readiness, emotional perception/regulation, executive cognitive performance, cortisol measures, treatment gain, treatment responsivity, treatment completion, Maryland Offender Based State Correctional Information System (OBSCIS) data, institutional infractions, segregations, and several other computed variables.